An empirical investigation on internet privacy on social network sites among Malaysian youths - Salleh, Norsaremah; Hussein, Ramlah; Mohamed, Norshidah (IGI Global, 2012)
People have been using Social Network Sites (SNS) to communicate and make friends online. Although SNS offer many benefits to users, information privacy seems to be overlooked. Based on the Protection Motivation Theory, this study investigated the factors that might influence youths to disclose information about themselves on the SNS. Four factors were investigated to determine whether there are significant relationships between them and information disclosure. The factors were perceived vulnerability, perceived severity, perceived benefits and selfefficacy. A self-administered questionnaire was developed to capture useful information pertaining to the subject matter. Using university students as sample, five hundred questionnaires were distributed and four hundred and eighty six were collected for further analysis. The results revealed that perceived vulnerability, perceived benefits and self-efficacy were significantly related to information disclosure, while perceived severity was not significantly related.